Consumption of Cross-Linked Resistant Starch (RS4XL) on Glucose and Insulin Responses in Humans - Enas K. Al-Tamimi; Paul A. Seib; Brian S. Snyder; Mark D. Haub (Journal of Nutrition and Metabolism)
Objective. The objective was to compare the postprandial glycemic and insulinemic responses to nutrition bars containing either cross-linked RS type 4 (RS4XL) or standard wheat starch in normoglycemic adults (n = 13; age = 27±5 years; BMI = 25±3 kg/m2). Methods. Volunteers completed three trials during which they consumed a glucose beverage (GLU), a puffed wheat control bar (PWB), and a bar containing cross-linked RS4 (RS4XL) matched for available carbohydrate content. Serial blood samples were collected over two hours and glucose and insulin concentrations were determined and the incremental area under the curve (iAUC) was calculated. Results. The RS4XL peak glucose and insulin concentrations were lower than the GLU and PWB (P<.05). The iAUC for glucose and insulin were lower following ingestion of RS4 compared with the GLU and PWB trials. Conclusions. These data illustrate, for the first time, that directly substituting standard starch with RS4XL, while matched for available carbohydrates, attenuated postprandial glucose and insulin levels in humans. It remains to be determined whether this response was due to the dietary fiber and/or resistant starch aspects of the RS4XL bar.